2011
DOI: 10.1136/jech.2010.113571
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of receptive and creative cultural activities and their association with perceived health, anxiety, depression and satisfaction with life among adults: the HUNT study, Norway

Abstract: This population-based study suggests gender-dependent associations between cultural participation and perceived health, anxiety, depression and satisfaction with life. The results support hypotheses on the effect of cultural activities in health promotion and healthcare, but further longitudinal and experimental studies are warranted to establish a reliable cause-effect relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
200
5
22

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(241 citation statements)
references
References 26 publications
14
200
5
22
Order By: Relevance
“…Cultural activities can thus be seen as a form of social capital that can be used as inputs in health production (e.g. Folland, 2008) Several empirical studies using individual-level survey data have found a positive association of cultural-event attendance with perceived health in various populations (Cuypers et al, 2012;Johansson et al, 2001;Khawaja and Mowafi, 2006;Renton et al, 2012;Wilkinson et al, 2007). It is questionable, however, whether the observed correlations reflect causal effects of arts participation on health.…”
Section: Previous Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Cultural activities can thus be seen as a form of social capital that can be used as inputs in health production (e.g. Folland, 2008) Several empirical studies using individual-level survey data have found a positive association of cultural-event attendance with perceived health in various populations (Cuypers et al, 2012;Johansson et al, 2001;Khawaja and Mowafi, 2006;Renton et al, 2012;Wilkinson et al, 2007). It is questionable, however, whether the observed correlations reflect causal effects of arts participation on health.…”
Section: Previous Literaturementioning
confidence: 99%
“…Furthermore, creative activities have been shown to be correlated with perceived health (e.g. Cuypers et al, 2012). On the other hand, other leisure-time activities could reflect time constraints that reduce the opportunities to engage in both cultural and health enhancing activities.…”
Section: Definition Of the Conditioning Setmentioning
confidence: 99%
See 1 more Smart Citation
“…fylkeskultursjef R. Kvalø) [15]. Data fra HUNT3 viste at de som var kulturelt aktive opplevde bedre helse, var mer tilfreds med livet sitt og erfarte mindre angst og depresjon [12].Definisjonen av kulturdeltagelse er imidlertid ikke enkel, saerlig når spørsmålene skal inkluderes i et spørreskjema som i HUNT. Også ved HUNT3 var det…”
unclassified
“…Ofte er antallet deltagere relativt lavt, og seleksjon er dessuten en utfordring, da det oftest ikke er tilfeldig hvem som deltar i slike studier. Sosioøkonomi er en viktig konfunderende faktor, etter som de med høy utdanning og inntekt oftere deltar i kulturaktiviteter, samtidig som de også har bedre helse enn de som har mindre utdanning og lavere inntekt [12]. Definisjonen av begrepene kultur og kulturdeltagelse kan variere fra studie til studie, og det er brukt ulike helsemål, slik at det ikke er lett å sammenlikne resultatene.…”
unclassified